Effect of terrestrial organic matter on ocean acidification and CO2 flux in an Arctic shelf sea. (June 2020) - Capelle, David W.; Kuzyk, Zou Zou A.; Papakyriakou, Tim; Guéguen, Céline; Miller, Lisa A.; Macdonald, Robie W.
Highlights: Terrestrial carbon remineralization reduces aragonite-saturation and increases pCO2 . Export production and terrestrial CaCO3 dissolution offset remineralization effects. Changes in marine pCO2 and ΩAr depend on watershed geology and organic matter C:N. Abstract: Recent research has focused on the changing ability of oceans to absorb atmospheric CO2 and the consequences for ocean acidification, with Arctic shelf seas being among the most sensitive regions. Hudson Bay is a large shelf sea in northern Canada whose location at the margin of the cryosphere places it in the vanguard of global climate change. Here, we develop a four-compartment box-model and carbon budget using published and recently collected measurements to estimate carbon inputs, transformations, and losses within Hudson Bay. We estimate the annual effects of terrestrial carbon remineralization on aragonite saturation (ΩAr, a proxy for ocean acidification) and on the partial pressure of CO2 (pCO2, a proxy for air-sea CO2 flux) within each compartment, as well as the effects of marine primary production, marine organic carbon remineralization, and terrestrial calcium carbonate dissolution. We find that the remineralization of terrestrial dissolved organic carbon is the main driver of CO2 accumulation and aragonite under-saturation in coastal surface waters, but this is largely offset by marine primary production. Below the surface mixed layer, marine organic carbon remineralization is the largest contributor to CO2 accumulation and aragonite under-saturation, and is partially offset by terrestrial CaCO3 dissolution. Overall, the annual delivery and processing of carbon reduces ΩAr of water flowing through HB by up to 0.17 units and raises pCO2 by up to 165 µatm. The similarities between Hudson Bay and other Arctic shelf seas suggest these areas are also significantly influenced by terrestrial carbon inputs and transformation.